MODELING OF SUPPLIES OF MATERIAL RESOURCES TO THE ENTERPRISE OF THE CHEMICAL INDUSTRY - Syardova, O.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
In a market economy, the main task of chemical industry enterprises is to increase the competitiveness of products. Its level is determined by the quality, the cost of providing it, the organization of production, including such economic indicators as reducing the time of supply of materials and components, determining the optimal volume of their stock, etc. Today, almost all modern enterprises of the chemical industry have switched to a "pulling" production system, in which production volumes depend on demand. At the same time, in order to draw up a production plan in advance, it is necessary to forecast the demand for products. In this regard, increasing the efficiency of enterprises and ensuring systemic stability in a competitive environment should be ensured by maximum coordination and integration of the procurement, production and sales links. It should be noted that chemical industry enterprises often face the problem of a large number of defective products and significant transportation costs. In addition, enterprises are forced to store significant volumes of purchased products. This problem arises due to inaccurate forecasts of demand and volumes of ordered raw materials from suppliers. One of the ways to reduce costs is to determine the optimal amount of supplies of material resources and time. The use of a modified method of multicriteria assessment using the method of constructing a decision tree will reveal the probabilities of critical and non-critical costs for an enterprise and, using appropriate approaches to choosing the best solution among a variety of alternatives, choose the one, following which will achieve the minimum costs.